La lectura y su incidencia en el proceso de enseñanza - aprendizaje de los estudiantes del sexto año de Educación General Básica de la Escuela "Gabriela Mistral" parroquia central, cantón Chillanes, provincia Bolívar, durante el año lectivo 2009 - 2010 - Baños Gaibor, Rosalva Janeth (2011)
This paper analyzes the relationship of reading in the teaching - learning of students of the sixth Year of General Basic Education Central Parish, Canton Chillanes, and Bolivar Province. Seized opportunities to optimize and innovate the socio context, in search of an atmosphere of respect, solidarity, cooperation and participation of all stakeholders in the educational group in the teaching - learning. To achieve the objectives of this paper conducted a quantitative research, field action and descriptive and explanatory levels, which were developed in four stages with their respective constituents: The Problem, Theoretical Framework, Methodology and Administrative Framework. In the first stage, implemented a community context analysis, literature review current authors on the subject. In addition we discussed clearly personal judgment according to our experience, it made possible to support the research work. In the theoretical framework we assume the concepts, theoretical and other elements, the scientific obtained helped us to articulate properly the assumptions and their respective variables to enable a clear and consistent benefit the fundamental achievement is improving reading for school performance of students are expected achievements. The methodology explained in detail the model used, the population or universe that consists of 61 students and 4 teachers selected according to the subject, making an exhibition of selected instruments and operating procedures. The data collection technique was used Survey applied to teachers, students gather the information you provided, at a time, that it was systematized in order to make that analysis and interpretation of results. The analysis and discussion of results are shown through charts, graphs and their interpretations, conclusions and recommendations, and testing the hypothesis using descriptive statistics on the percentage method supported this research not only aims to reach the the conclusions and recommendations, but to make a proposal, after the analysis done on the basis of the results globally. It is an important proposal to start a new stage of educational development, efforts are made to reverse this situation will enable to have an educated population that can adequately address the challenges posed by the ongoing process of liberalization and globalization of the economy. Propose solutions and expected achievements of the various actors that make up the institutional pedagogical collective, therefore, are public guidance indicating the goals to be achieved to get a quality education. Check the knowledge, skills and attitudes of those involved in education (students, teachers), the same as evidence in actions and performances that can be observed and evaluated in the contexts in which these are developed.